2011
DOI: 10.1038/oby.2011.248
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between Leptin Levels and Sleep Duration or Quality in Obese Adults

Abstract: Previous research in lean subjects has found lower leptin levels associated with shorter sleep duration. Since leptin levels are higher and some of the actions of leptin are impaired in obese individuals, one cannot assume that sleep will be similarly associated with leptin in obese individuals. The aim of this paper was to examine the cross-sectional association between habitual sleep duration and quality and plasma leptin levels in a sample of 80 obese men and premenopausal women aged 18–50 years. Leptin lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 17 publications
(26 reference statements)
3
28
2
1
Order By: Relevance
“…Although it has been suggested that sleep restriction acutely reduces concentrations of leptin and increases concentrations of ghrelin, differences in leptin concentration have not been seen in all crosssectional studies 38 nor have changes in leptin concentration been found in all acute sleep-restriction studies. 39 We found no changes in leptin nor ghrelin concentration after 8 days of sleep restriction.…”
Section: Discussionmentioning
confidence: 91%
“…Although it has been suggested that sleep restriction acutely reduces concentrations of leptin and increases concentrations of ghrelin, differences in leptin concentration have not been seen in all crosssectional studies 38 nor have changes in leptin concentration been found in all acute sleep-restriction studies. 39 We found no changes in leptin nor ghrelin concentration after 8 days of sleep restriction.…”
Section: Discussionmentioning
confidence: 91%
“…Specifically, the larger Wisconsin study showed that 5-h sleep/ night was associated with a 15.5% lower morning serum leptin level and 14.9% higher ghrelin level compared with 8-h sleep/night, independent of BMI and gender. The third study did not show any association between sleep duration measured actigraphically and morning leptin levels (relative to body fat percentage), but in contrast to the previous two reports, it studied a smaller (n ϭ 80), predominantly female (75%), sleep-restricted and obese (mean BMI ϭ 38 kg/m 2 ) cohort (93). Although sleep was measured more precisely in this last study, it seems unlikely that this increased accuracy would have compensated for the 10-fold smaller sample size.…”
Section: Appetite Regulation-leptinmentioning
confidence: 89%
“…Leptin has been postulated as a possible mechanistic link between habitual sleep duration, obesity, and insulin resistance (48, 84, 86 -92). Four cross-sectional epidemiological studies have examined the relationship between sleep duration, leptin, and obesity (48,50,93,94). The two larger studies both relied on self-reported sleep duration (48,50) and showed in the populationbased Wisconsin Sleep Cohort Study (48) of 1024 individuals (54% male), as well as the community-based Quebec Family Study (50) of 740 individuals (44% male), that short sleep was associated with reduced blood leptin.…”
Section: Appetite Regulation-leptinmentioning
confidence: 98%
“…In a cross-sectional study of actigraphy-measured sleep, Knutson et al 37 reported no association between sleep duration, efficiency or disturbances and leptin. In intervention studies, Nedeltcheva et al 22 and Schmid et al…”
Section: What Hormonal Controls Involved In the Regulation Of Energy mentioning
confidence: 99%